Alkaline Earth Metal Template (Cross‐)Coupling Reactions with Hybrid Disila‐Crown Ether Analogues. Issue 69 (4th November 2019) - Dankert, Fabian; Donsbach, Carsten; Rienmüller, Julia; Richter, Roman M.; von Hänisch, Carsten
Abstract: Alkaline earth metal iodides were used as templates for the synthesis of novel silicon‐based ligands. Siloxane moieties were (cross‐)coupled and ion‐specific, silicon‐rich crown ether analogues were obtained. The reaction of 1, 2, 7, 8‐tetrasila[12]crown‐4 (I ) and 1, 2‐disila[9]crown‐3 (II ) with MgI2 yielded exclusively [Mg(1, 2, 7, 8‐tetrasila[12]crown‐4)I2 ] (1 ). The larger Ca 2+ ion was then employed for cross‐coupling of I and II and yielded the complex [Ca(1, 2, 7, 8‐tetrasila[15]crown‐5)I2 ] (2 ). Cross‐coupling of I and 1, 2, 4, 5‐tetrasila[9]crown‐3 (III ) with SrI2 enables the synthesis of the silicon‐dominant 1, 2, 4, 5, 10, 11‐hexasila[15]crown‐5 ether complex of SrI2 (3 ). Further, the compounds [Sr(1, 2, 10, 11‐tetrasila[18]crown‐6)I2 ] (4 ), [Sr(1, 2, 13, 14‐tetrasila[24]crown‐8)I2 ] (5 ), and [Sr(1, 2, 13, 14‐tetrasila‐dibenzo[24]crown‐8)I2 ] (6 ) were obtained by coupling I, 1, 2‐disila[12]crown‐4 (IV ) or 1, 2‐disila‐benzo[12]crown‐4 (V ), respectively. Using various anions, the (cross‐)coupled ligands were also observed in an X‐ray structure within the mentioned complexes. These template‐assisted (cross‐)couplings of various ligands are the first of their kind and a novel method to obtain macrocycles and/or their metal complexes to be established. Further, the Si−O bond activations presented herein might be of importance for silane or even organic functionalization. Abstract : Templated synthesis : Alkaline earth metal iodides were used as templates for the synthesis of novel silicon‐based ligands. Siloxane moieties were (cross‐)coupled and ion specific, silicon‐rich crown ether analogues were obtained. The coupling of various ligands gives an outlook on Group 2 ion‐catalyzed macrocycle and/or silane syntheses.